Assessment of animal welfare in dairy cows in a farm of Comarca Lagunera, México - Alejos-De la Fuente, José Isidro; Sosa-Montes, Eliseo; Guzmán-González, Beatriz; Peralta-Ortiz, Jesús Germán; Almaraz-Buendía, Isaac; Torres-Cardona, María Guadalupe (Ecosistemas y Recursos Agropecuarios, 2025)
The aim of this study was to evaluate the animal welfare status of dairy cows in an intensive production unit, using the Welfare Quality protocol. A total of 315 lactating and dry cows were evaluated, based on four principles: adequate feeding, housing, health and behavior. To achieve this, animal-based, management-based and housing-based measures were recorded. As indicated in the protocol, most of them contain a three-point scale ranging from zero to two, 0: welfare is good, 1: there is some compromise in welfare and 2: welfare is insufficient and unacceptable. The critical variables found for cow welfare were: absence of thirst; cleanliness of quarters (46.62%), udder (13.42%) and flanks (38.34%); time to lie down (5.24 s); dystocia (24%), eye discharge (6.27%) and diarrhea (100%). It is concluded that the production unit has important areas of opportunity to improve the animal welfare of its cows, according to the standards proposed by the Welfare Quality protocol.